The Effects of Derivatives on Asset Price Volatility: A Study on the Options Trading in the USA and UK (Journal of Asian Development Studies, 2024)
The impact of options trading on underlying asset prices in the United States and United Kingdom markets from 2010 to 2024 is the focus of this study. A multivariate GARCH model and Granger causality tests were used to analyze the relationship between options trading volume and price volatility of the underlying assets. Results indicated a significant bidirectional relationship between options trading activity and asset price volatility, with increased options volume generally associated with higher short-term price fluctuations. The comparison between the USA and UK markets provides valuable insights into how different regulatory environments and market structures may impact the relationship between derivatives and asset prices. However, the long-term impact on price efficiency across various market segments showed mixed results. This research paper provides regulatory policies regarding the role of derivatives in financial markets that policymakers in the USA and the UK should implement. The findings could have implications for risk management practices, market stability, and the design of financial instruments